Speaking from above and below - The Gospel of John as metaphorical and narrative reference to a distant reality - Rahmsdorf, Olivia Luisa (2018)
The one who is from the earth belongs to the earth and speaks from the earth (Jn 3:31). How can one speak from the earth and at the same time about heavenly things? The Fourth Gospel (FG) creates a tension between these two realms of perception and cognition. To reach beyond or above the earth we have to transcend time and space, our individual context and limited visual horizon. To overcome the obstacle of confined space we can rely on metaphors since their key faculty is to transport (μετα-φέρω). To transcend the limitations of time we can recruit the genre of narration. These two modes of references to a reality that is located and dated beyond our realms are at work in the FG. With Ricoeur's theoretical assistance, these features of the FG are highlighted as the prerequisite for its synthesis of the heterogeneous: above and below, light and darkness, spirit and flesh.
Keywords: Above and Below; Gospel of John; Metaphors and Narratives; Paul Ricoeur; Space and time